1992
DOI: 10.1177/001789699205100304
|View full text |Cite
|
Sign up to set email alerts
|

Diet, obesity and being overweight: a qualitative research study

Abstract: LAY perceptions of being overweight or obese were examined in qualitative one-to-one interviews and group discussions conducted with people who were overweight, obese or slimmers. Many dieters re ported being caught in cyclical patterns of weight loss followed by weight gain. Successful slimmers were aware of the need to make long-term changes to their diet. The challenge facing health educators is to develop new materials or initiatives which en courage and support long-term adjustments to eat ing behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…9,28,29 This type of information can also be important in tailoring prevention and secondary prevention activities that resonate with the experiences of different population subgroups. Qualitative investigations enable us to look for more detailed information within subgroups to help identify where groups may be similar and/or different, and where further work may need to occur to improve understanding of certain subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,28,29 This type of information can also be important in tailoring prevention and secondary prevention activities that resonate with the experiences of different population subgroups. Qualitative investigations enable us to look for more detailed information within subgroups to help identify where groups may be similar and/or different, and where further work may need to occur to improve understanding of certain subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…As in other studies, men preferred to focus on physical activity rather than dieting as a way to lose or maintain weight. 29,41,42 Part of this was because men wanted to be engaged in activities that made them feel more masculine -fitter, stronger, and more muscular. They also felt that their identities as men were threatened by the concept of dieting, which was often marketed to and used by women.…”
Section: Discussionmentioning
confidence: 99%
“…The research is also unclear about whether being obese affects young people's self-esteem (French et al, 1995;Klesges et al, 1992;Rumpel and Harris, 1994), but fat people certainly face discrimination (Gortmaker et al, 1993). Obese and overweight adults in one qualitative study had clearly internalised society's negative image of them (Barker and Cooke, 1992). There is less research on the characteristics of those holding prejudicial views towards obese people, but these views tend to be held by those who are also racist, politically conservative and moralistic, according to one US study (Crandall and Biernat, 1990).…”
mentioning
confidence: 99%
“…High rates of eating disorders among UK Asian girls have been found (Mumford et al, 1991;Ahmad et al, 1994a), together with concerns about body shape (Hill and Bhatti, 1995). For girls and women, the reasons given for dieting are to do with body image rather than with health (Barker and Cooke, 1992). Evidence indicates that there is widespread dissatisfaction with body and weight among girls and women in Westernised countries, and that gender differences are often not given enough attention in programmes promoting healthy eating (Dixey, 1996).…”
mentioning
confidence: 99%
“…The same features are found among British ethnic minorities; thus Mumford and Whitehouse [14] found high rates of eating disorders among Asian girls. As with younger females, the reasons adult women give for dieting are to do with body image rather than with health [15]. Fairburn and Cooper's [16] community sample of 369 women and 35 bulimic women found that 90 per cent of the total wished to weigh less than the population average; 59 per cent of girls and young women aged 11-18 in a sample in London said they wished to lose weight [17].…”
Section: "Eating Disorders"mentioning
confidence: 99%